The misalignment between accounting faculty perceptions of success and organizational image during a process of institutional change - Nova, S. C.; Lourenço, I. C.; Azevedo, R. F. L. (International Journal of Organizational Analysis, 2018)
Purpose This study analyzes the impacts of an institutional change process on a specific higher education institution in Europe, and the trade-offs between the faculty perceptions of success and the organization image during this process, in light of the identity institutional theory. Design/methodology/approach The impacts of this institutional change are analyzed and discussed based on in-depth interviews conducted with faculty members of the Accounting Department in which they reflected upon academic success vis-a-vis the career assessment system adopted, followed up by those faculty members’ answering an electronic questionnaire about organizational identity and image perception (Gioia, Schultz, & Corley, 2000). Findings Considering the individual perspectives, faculty are concerned about their vocations and aspirations, with feelings of apprehension and insecurity, perceiving the institutional goals as too high and potentially unattainable. By shifting the priority towards research, costs in terms of losing the institutional excellence in teaching might arise, which has been traditionally keen to the Institute’s organizational identity and consistent with faculty’s perceptions of academic success. Research limitations/implications As in any research endeavour, some limitations might emerge. First, we addressed the context of a specific business school, in a European country. It is certainly true that culture plays a role in terms of both the organization and the country cultures. We acknowledge this as a limitation. Nevertheless, this research takes a “local” stance, the logic of academic evaluation and its impacts on institutional and individual identity formation processes is a worldwide phenomenon. Secondly, in defining our selection criteria, we excluded the possibility of other voices to be heard, both in the Department itself and in the Business School. Regarding the Department, we argue that those are the ones who could influence future decisions, considering that they are the only ones eligible for the governing bodies under the Institute’s regulations. Regarding the Business School, adding other Department(s) means adding other discipline(s) to our analysis with specific and different dynamics of researching, publishing, and teaching, which also impacts the expectations regarding career and academic success. Practical implications First, before beginning an institutional change process, it is necessary to assess the vocations and aspirations of its members. The solution requires to reanalyze academic career premises and to reconsider the weights given to each academic activity, or furthermore, to offer more than one career path, so as to make it flexible for each faculty to follow their vocations and aspirations or to adapt to life demands. Secondly, in terms of organizational identity and image, the challenge is to minimize the gap between the construed external image and the internal identity, striving to achieve a balance between teaching, research, outreach and service. Originality/value Because of the very nature of the academic work, we propose that the application of the theory should be preceded by a careful consideration of what is academic success. The misalignments studied and reported here reveals a multilevel phenomenon, wherein individual academic identities are often in conflict with the institutional image. Our study entails a contribution to the application of the identity institutional theory to academic institutions.